Pengaruh Kualitas Sumber Daya Manusia, Implementasi Sistem Informasi Manajemen Daerah Dan Penerapan Standar Akuntansi Pemerintah Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Meisy Hendri; Erinos NR (Universitas Negeri Padang, 2020)
This study aims to empirically pirove the influence of the quality of human resources, the implementation of regional management information systems (SIMDA) and the application of government accounting standards to the quality of local government financial reports. This research is causative research. The population in this study was 39 Regional Organizations (OPD) of West Sumatra Province. The sample in this study used the Total Sampling method. The type of data used in this study is primary data. Data collection techniques using a questionnaire consisting of 3 respondents in each OPD so that the questionnaire distributed was 117 questionaires. The analytical method used is Multiple Regression Analysis using SPSS version 20.00. The results showed: the quality of human resources, implementation of regional management information systems and the application of government accounting standards have a positive effect on the quality of local government financial reports.